Life cycle environmental impacts of inhalers. (10th November 2019) - Jeswani, Harish Kumar; Azapagic, Adisa
Abstract: Pressurised metered-dose inhalers are a method of choice for delivering drugs into lungs for the treatment of asthma and chronic obstructive pulmonary disease across the globe. HFC-134a and HFC-227ea propellants, which are currently used in these inhalers, have significant global warming potentials. To reduce the climate change impact of inhalers, several options are available to the industry, including alternative devices, such as dry powder inhalers and nebulisers. In addition, the manufacturers can reduce the propellant quantity per dose or use a different propellant with a lower global warming potential, such as HFC-152a. This study evaluates the life cycle environmental impacts of different types of inhaler and investigates possible scenarios to reduce their impacts. The environmental impacts are estimated through life cycle assessment, following the ReCiPe impact assessment method. The results suggest that HFC-152a inhaler has the lowest impacts for ten out of 14 categories considered, while the dry powder inhaler is the worst option for eight impacts; however, it has the lowest climate change and ozone depletion impacts. Considering the annual use of pressurised metered-dose and dry powder inhalers in the UK, they generate 1.34 Mt CO2 eq., largely due to HFC-134a inhalers. This represents 4.3% of greenhouse gas emissions of the NHS (National Health Service). Replacing HFC-134a with HFC-152a would reduce the climate change and ozone depletion impacts of inhalers in the UK by 90%–92%. Most other environmental impacts would also decrease significantly (28%–82%). Switching from pressurised metered-dose inhalers to dry powder inhalers would lead to an even higher reduction in the climate change impact (96%). However, several other impacts would increase significantly, including human toxicity, marine eutrophication and fossil depletion. Since changing propellants or replacing pressurised metered-dose inhalers with dry powder inhalers requires further research and development, pharmaceutical companies should continue to work on minimising propellant usage in inhalers and on achieving higher rates of recycling of current inhalers. Graphical abstract: Image 1 Highlights: HFC-152a inhaler has the lowest impacts for ten out of 14 categories considered. Dry powder inhaler has the lowest GWP but is the worst option for eight other impacts. The use of inhalers in the UK generates 1.34 Mt CO2 eq./yr due to HFC-134a inhalers. Replacing HFC-134a and HFC-227ea with HFC-152a would reduce GWP by 92%. Most other environmental impacts would also decrease significantly (28%–82%).